Primary study on screening of optimum Stropharia rugoso-annulata strains and suitable cultivation medium with Zizania latifolia leaves - Zhou Zufa; Yan Jing (浙江大学学报. 农业与生命科学版)
Stropharia rugoso-annulata is an edible fungi with strong physiological activity and resistance, which can be cultivated by using rice straw, water bamboo leaves, wheat straw, and other agricultural waste resources. Zizania latifolia is the largest in the planting area of aquatic vegetables in Zhejiang Province, which was developed rapidly in recent years, and the area was more than 2 667 million square meters. Consequently, a large area of water bamboo planting has produced large amounts of water bamboo leaves, which is a waste of resources and environmental pollution by dumping and incineration, resulting in ecological and economic pressure. At present, the use of rice straw in planting S. rugoso-annulata has been already very mature. In this study, the best cultivation scheme and formula was determined through the comparison of applying different proportions of water bamboo leaves in the culture of S. rugoso-annulata strains, with the rice straw as the control, in order to provide scientific basis for production of S. rugoso-annulata.In order to improve the cultivation of S. rugoso-annulata and reduce the pollution caused by Z. latifolia leaves, three different S. rugoso-annulata strains were cultivated on seven mediums containing different proportions of Z. latifolia leaves to select the best strain and suitable cultivation medium.The results indicated that strain A1 showed the best mycelial growth and yield, followed by strain A2 and A3. Z. latifolia leaves affected the growth of S. rugoso-annulata in a certain degree, especially for mycelial growth, but no significant effect (P<0.05) was observed when the proportion was less than 60%. Therefore, the strain A1 cultivated on substrates with no more than 60% of Z. latifolia leaves would be an appropriate cultivation pattern, which can make full use of the wasted Z. latifolia leaves without significantly affected yield of S. rugoso-annulata.It is suggested that the leaves of Z. latifolia are not a good resources for S. rugoso-annulata cultivation, but it can reduce pollution caused by wasted Z. latifolia leaves.